Strategi dan Dampak Kenaikan Harga Kedelai Terhadap Pendapatan Pengrajin Tempe Di Tenggilis Mejoyo Surabaya - Imron Febrianto; Iswati Iswati; Emilia Pranata (Jurnal Manajemen Kreatif dan Inovasi, 2024)
This research aims to determine the strategies used by tempe craftsmen through the production process regarding the impact of rising soybean prices and to find out whether the income of tempe craftsmen due to the increase in soybean prices has changed in Tenggilis Mejoyo Village, Surabaya City. In conducting this research, the descriptive qualitative method was used by the researcher. The findings in this research are how the tempeh production process, the strategies used by tempeh craftsmen to overcome the increase in soybean prices and the increase in soybean prices affect the income of tempeh craftsmen. It is hoped that this research will provide benefits, especially for all elements of society, for theoretical and practical benefits. The research results show that reducing the size of tempeh sold at a fixed price is a way for tempeh craftsmen to overcome the decline in income. The increase in soybean prices not only affects the income of tempeh craftsmen but also affects the amount of tempeh production which decreases by 50%. Some of the suggestions offered by researchers include craftsmen expanding tempe marketing, for the Indonesian government to help resolve the problem of rising prices of basic commodities, especially soybeans, which are still unstable, and for researchers who can then carry out further research on the impact of rising soybean prices on the purchasing power of tempeh. community in Tenggilis Mejoyo Village, Surabaya City.